Correlation between Serum Krebs von den Lungen-6 Levels with Forced Vital Capacity and Modified Rodnan Skin Score of Patients with Restrictive Lung Disease in Diffuse-Type Systemic Sclerosis - Herlina Yani; Sumartini Dewi; Andri Reza Rahmadi (Indonesian Journal of Rheumatology, 2019)
Background Pulmonary fibrosis / intersitial lung disease (ILD) in systemic sclerosis (SSc) is a complicated restrictive pulmonary disease and the leading cause of disease-related mortality. Progressive skin fibrosis in diffuse-type SSc (dSSc) is associated with decreased forced vital capacity (FVC). Modified Rodnan Skin Score (mRSS) examination is used as a parameter to assess skin fibrosis, while high-resolution computed tomography (HRCT) and pulmonary function tests (PFTs) are used to assess pulmonary fibrosis. The HRCT test remains as the gold standard in diagnosing ILD. However, it costs a lot and is not available in all healthcare facilities. Krebs Von den Lungen-6 (KL-6) is a biomarker to evaluate pulmonary fibrosis. The aim of this study was to analyze the correlation of serum KL-6 levels with FVC and mRSS value of patients with restrictive lung disease in dSSc. Method This was a cross-sectional study that used primary data from dSSc patients who visited rheumatology outpatient clinic in Hasan Sadikin Hospital Bandung, Indonesia, during the period of June-July 2019. History taking, physical examination, mRSS, spirometry, and serum KL-6 levels were performed. Data were analyzed using the Rank Spearman correlation test. Result There were 27 subjects with the mean age of 42 Â± 12 years. Based on FVC (%) restrictive lung disease criteria, the majority of subjects (74.1%) had severe restrictive lung disease and the rest of all subjects (25.9%) were non severe restrictive lung disease. Serum KL-6 levels ranged from 0.545 to 8.138 ng/ml. The results showed that there was no correlation between serum KL-6 levels and FVC values (r = -0.118, p = 0.279) and mRSS (r = 0.101, p = 0.312 ). Conclusion There is no correlation between serum KL-6 levels with FVC and mRSS value of patient with restritive lung disease in diffuse type systemic sclerosis. Keywords : diffuse type systemic sclerosis, Forced Vital Capacity, KL-6, mRSS, restrictive lung disease.